ZrSi2–MgO as novel additives for high thermal conductivity of β‐Si3N4 ceramics - Wang, Weide; Yao, Dongxu; Chen, Huanbei; Xia, Yongfeng; Zuo, Kaihui; Yin, Jinwei; Liang, Hanqin; Zeng, Yu‐Ping (Journal of the American Ceramic Society, 2020)
A novel ZrSi2–MgO system was used as sintering additive for fabricating high thermal conductivity silicon nitride ceramics by gas pressure sintering at 1900°C for 12 hours. By keeping the total amount of additives at 7 mol% and adjusting the amount of ZrSi2 in the range of 0‐7 mol%, the effect of ZrSi2 addition on sintering behaviors and thermal conductivity of silicon nitride were investigated. It was found that binary additives ZrSi2–MgO were effective for the densification of Si3N4 ceramics. XRD observations demonstrated that ZrSi2 reacted with native silica on the Si3N4 surface to generate ZrO2 and β‐Si3N4 grains. TEM and in situ dilatometry confirmed that the as formed ZrO2 collaborated with MgO and Si3N4 to form Si–Zr–Mg–O–N liquid phase promoting the densification of Si3N4. Abnormal grain growth was promoted by in situ generated β‐Si3N4 grains. Consequently, compared to ZrO2‐doped materials, the addition of ZrSi2 led to enlarged grains, extremely thin grain boundary film and high contiguity of Si3N4–Si3N4 grains. Ultimately, the thermal conductivity increased by 34.6% from 84.58 to 113.91 W·(m·K)−1 when ZrO2 was substituted by ZrSi2. The figure in the left shows the original state of the green compact including alpha‐silicon nitride with a thin SiO2 film and sintering additives (ZrSi2 and MgO). The figure in the middle shows the β‐Si3N4 grains were in situ generated by the reaction between ZrSi2 and native SiO2. Thus, abnormal grain growth was promoted by in‐situ generated β‐Si3N4 grains. The figure in the right shows a bimodal microstructure composed of a fraction of large elongated grains and a majority of fine matrix grains was achieved in densified samples.